(untitled) (American Journal of Islam and Society, 2020)
Since its 2013 release, Wael Hallaq’s The Impossible State has retained a central position in debates within the field of Islamic political thought. While Joseph Kaminski mostly agrees with Hallaq’s central thesis that an Islamic state is a contradiction in terms (as a modern state is in its very constitution immoral and ergo non-Islamic), he aims in his The Contemporary Islamic Governed State: A Reconceptualization to shift the discussion away from government to governance. To read the full book review, download the PDF file on the right.